Digitalization impact on work quality at the enterprise operational level - Tverdushka, Tetiana; Stoliaruk, Khristina (Technology audit and production reserves, 2020)
The object of research is the work quality of operational staff. One of the most problematic places in the introduction of new production technologies is the adaptation of personnel to digital transformation. Understanding and systematic management actions of managers can lead the company to business growth, make it more flexible through the proper use of digitalization as a potentially important component of business strategy. Methods of logical generalization and analysis are used in the analysis of literature sources on the research topic. The work quality at the enterprise operational level was considered in two dimensions: the quality of work results and the quality of working life. During the sociological study at machine-building enterprises is developed a conceptual model of the interaction between work tasks, methods of labor organization and technological tools. According to the expert potential consequences assessment of the impact of digitalization on the operational staff work quality, the highest scores are given to the following factors: work intensity; content of work tasks; control over work; learning; motivation and work life balance; health; rights; career management. The Analytical Hierarchy Process, which allows to determine the components of the adaptation system of personnel to digital information and to form an algorithm for choosing the optimal version of the system for the enterprise, is also used. The results of the presented study confirm the insufficient level of workers and industrial engineers readiness to implement changes related to the use of digital tools. The results provide a practical basis for the enterprises management to form a hierarchical structure of employee adaptation system to digital transformation. Presented system will be the projects framework for production technologies modernization, labor processes improving, staff training and the successful implementation procuring of digital transformation based on the model of interaction between work tasks, methods and technological tools at the operational level of the enterprise.